2015
DOI: 10.1088/0268-1242/31/1/014002
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer during metal-assisted and stain etching of silicon

Abstract: The etching of silicon in fluoride solutions is limited by the kinetics of charge transfer not thermodynamics. This characteristic is what gives fluoride etching its great versatility in making different types of nanostructures as the result of self-limiting chemistry. This review approaches the kinetics of electron transfer from silicon and metal coated silicon to a solution phase species from a fundamental point of view in order to establish a better understanding of the mechanisms of nanostructure formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 63 publications
0
19
0
1
Order By: Relevance
“…Both local and remote etching can take place depending on reaction conditions (Chartier et al, 2008; Chiappini et al, 2010). Many aspects of the mechanism of catalysis remain unresolved because of uncertainties in the electronic structure of the metal/semiconductor interface and its role in electron transfer (Kolasinski, 2014, 2016). The vertical direction and its relationship to crystallographic axes are defined readily during the etching of flat single-crystal wafers.…”
Section: Introductionmentioning
confidence: 99%
“…Both local and remote etching can take place depending on reaction conditions (Chartier et al, 2008; Chiappini et al, 2010). Many aspects of the mechanism of catalysis remain unresolved because of uncertainties in the electronic structure of the metal/semiconductor interface and its role in electron transfer (Kolasinski, 2014, 2016). The vertical direction and its relationship to crystallographic axes are defined readily during the etching of flat single-crystal wafers.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand why and how the pore morphology changes with the type and level of doping, a modeling describing the silicon bands modulation around nanometer sized silver and electrolyte contacts has been carried out. This type of modeling has already provided insights into the photo/electrochemical behavior of metal decorated silicon electrodes (Nakato et al, 1988 ), on MACE (Kolasinski, 2016 ) and electrochemically assisted MACE mechanisms (Chourou et al, 2010 ; Huang et al, 2010 ; Torralba et al, 2016 ; Bastide et al, 2019 ). The results have also been interpreted in the light of data from the large literature existing on the electrochemistry of silicon in HF media, in particular the reference book by Lehmann ( 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, band-bending at the metal/Si interface and polarization of the Si substrate has been considered as important factors in the metal-assisted etching. 36,40,46,[49][50][51][52][53] For example, Kolasinski 51,53 proposed the mechanism of the metal-assisted etching with the calculation of the band structures at the metal/Si interface formed by different kind of metals. He demonstrated that the band structure is favorable for the hole injection in the cases of Au and Pt with large work functions but not in the case of Ag with relatively small work function.…”
Section: Formation Of Mesoporous Layermentioning
confidence: 99%